Struktur Dramatik Lakon “Retna Paniti” dalam Pertunjukan Wayang oleh Mariyanto - Nugraha, Pulung Wicaksana; Sunardi, Sunardi; Samodro, Wisnu; Wicaksono, Andi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to reveal and describe the dramatic structure of the Retna Paniti play as performed by Mariyanto, a puppeteer from Ngawonggo, Klaten. The research was conducted because the performance presents a distinctive dramatic form that differs from the conventional structure of the Surakarta-style pakeliran. This study employs a qualitative approach with a descriptive-analytical method, focusing on the analysis of scene sequences and the interrelation among dramatic elements. Data were collected through literature review, observation of the 2018 performance recording, and in-depth interviews with informants familiar with Mariyanto’s puppetry style. The findings indicate that the dramatic structure of Retna Paniti in Mariyanto’s version follows a pattern close to Freytag’s Pyramid theory, yet adapted to the folk puppetry tradition of the Ngawonggo substyle. The performance opens with the battle scene between Gatotkaca and Baladewa, creating immediate tension, which contrasts with the Surakarta-style convention that typically begins with the jejer scene. The dramatic flow progresses from exposition to falling action and culminates in the achievement of harmony. The central theme emphasizes ethical values concerning harmony, loyalty, and self-control in social life, maintaining its relevance in contemporary society.